There is more than one way of feeding carnivorous fish: Surubim (Pseudoplatystoma reticulatum × P corruscans) are able to cope with carbohydrates rich diets, but there is a trade-off between growth and immunity - Sousa, Luana Camargo [UNESP]; Moromizato, Basia Schlichting [UNESP]; Almeida, Viviane do Nascimento Santana de [UNESP]; Miasaki, Celso Tadao [UNESP]; Takahashi, Leonardo Susumu [UNESP]; Biller, Jaqueline Dalbello [UNESP] (Elsevier, 2020)
Carnivorous fish require diets with high protein content to support adequate growth, improve health status and the production of antioxidants and the ability to respond to adverse environmental conditions. However, different protein-to-carbohydrate ratios can lead to different growth responses as a result of the administration of carbohydrates rich diets for carnivores fishes. In this study, we examined the effect of diets with different levels of dietary protein (P) and carbohydrate (CH) (38 P/22CH; 38 P/26CH; 38 P/30CH; 42 P/22CH; 42 P/26CH; 42 P/30CH) and the immunological and hematological responses and growth performance of surubim (Pseudoplatystoma reticulatum x P corruscans) (mean initial weight 23.08 ± 0.84 g) challenged with lipopolysaccharide (LPS). High levels of dietary protein (42 % P) did not improve growth performance and, regardless of CH content, did not affect oxidative stress. High levels of dietary carbohydrate increased lysozyme production and blood variables were increased after LPS challenge, without impairing the immune response. Diets with different protein-to-carbohydrate ratios can lead to distinct physiological responses in fish which can, as a consequence, differentially impact yield, indicating that there is more than one way of feeding carnivorous fish within a safe protein inclusion range (38–42 % P).
Keywords: Carnivorous fish; Growth; Immune response; Oxidative stress; Protein